PENERAPAN METODE PEER TEACHING PADA MATA KULIAH KAPITA SELEKTA MATEMATIKA PENDIDIKAN MENENGAH UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA TERHADAP KISI-KISI SOAL UN MATEMATIKA SMP - Zuli Nuraeni (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2017)
AbstractThis research is a class action research (CAR) with research subject of student of semester 3 of mathematics education of STKIP Muhammadiyah Kuningan. This study aims to determine the implementation of peer teaching method (peer tutoring) in the subjects of Kapita Selekta Mathematics for Junior High Schooll students of third semester of STKIP Muhammadiyah Kuningan to improve students' understanding of the lattice national test about the mathematics of junior high school. In the pre test the average score achieved was 59.17, the students understanding about the lattice about the mathematics of junior high school at the time of pre test of 66.67 including good criteria and 33.33% including enough criteria. In post test cycle I average value is 75,83, student understanding about lattice about mathematics of junior high school at post test cycle I as much 66,67 including criteria very good and 33,33% including good criterion. In post test cycle II average value is 75,83, student understanding about lattice about UN mathematics junior high school at post test cycle as much as 66,67 including criteria very good and 33,33% including good criterion. The average increase that occurred from pre-test to post-test cycle II that is equal to 16,67 or equal to 28,17%. Keyword: CAR, peer teaching, understanding math.